Pengaruh Desentralisasi Fiskal,Investasi Publik dan Investasi Swasta Terhadap Efektivitas Implementasi Otonomi Daerah di Kabupaten/Kota Provinsi Sumatera Barat - Luthfi Chalis Shiraath; Ali Anis (Universitas Negeri Padang, 2023)
This study is aimed to determine the influence of fiscal decentralization, publicinvestment, and private investment on the effectiveness of the implementationof regional autonomy of regencies or cities in West Sumatra province. The typesof this research are descriptive and inductive. This study used secondary paneldata sources from the Central Statistics Agency and the Directorate General ofFiscal Balance with cross-sections of 19 regencies and cities in West Sumatraand a time series from 2013 to 2021. The analysis in this study is a panel dataregression analysis. The results of this study found that: (1) fiscaldecentralization has a positive and significant effect on the effectiveness ofregional autonomy implementation;(2) public investment has a positive andinsignificant effect on the effectiveness of regional autonomy implementation;and lastly, (3) private investment has a positive and significant effect on theeffectiveness of regional autonomy implementation.